Knowledge, Perception and Practice of Safety Measures Related to Workplace Hazards among Manual Stone Crushing Workers in Sokoto, Nigeria - Kaoje, Aminu U.; Haliru, Ladan; Raji, Mansur O.; Ango, Umar M.; Ango, Jessica T. (International Journal of Occupational Safety and Health, 2018)
Background: Although manual stone crushing activities provide income to families, the working conditions are often unhealthy and dangerous and employees are ignorantly exposed to different hazardous materials particularly dust particles. Objectives: To assess Knowledge, perception, and Practice of occupational safety measures related to workplace hazards among manual stone crushing workers. Methods: A descriptive cross-sectional study was conducted among 156 informal small-scale quarries for construction materials workers in Sokoto metropolis. The respondents were selected using a simple random sampling technique and data collected using interviewer-administered questionnaires. Descriptive, bivariate and binary logistic regression analyses were performed using Statistical Package for Social Sciences version 23 and results presented in tables. Results: Respondents median age was 23 years, interquartile range: 18.3 – 28.0. Adolescents and young adults accounted for 54.4% of the workforce. All the respondents were males and 69.9% had no formal education. Only 25% had good knowledge of workplace hazard and as high as 63% have a low-risk perception of the hazards. Very few (7.7%) reported the use of personal protective equipment. Only awareness of disease risk (aOR =5.25, P <0.001) was the predictor of respondents’ knowledge of workplace hazards. Predictors for risk perception level of workplace hazards were respondents’ knowledge (aOR = 0.33, p˂0.01); Aware of risk of disease (aOR =2.92, P <0.01); and employment status (aOR = 0.31, p˂0.03). Conclusions: Poor knowledge and low-risk perception of workplace hazards are very prevalent among workers and very few reported use of personal protective equipment. Training and awareness creation on workplace hazards are highly recommended.